Faktor-Faktor Yang Berhubungan Dengan Status Gizi Pada Balita Usia 1-5 Tahun Di Wilayah Kerja Puskesmas Haurpanggung Kabupaten Garut - Nurjaman, Iman; Anjani, Tita (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
The main focus of nutritional problems today is low nutritional status because almost throughout Indonesia there are people with low nutritional status, especially toddlers. In the working area of the Haurpanggung Health Center, it was noted that there were still many under-five children who were malnourished, with a prevalence of malnutrition of 5.4% and undernutrition of 13.0%. This study aims to determine the factors related to the nutritional status of toddlers aged 1-5 years in Haurpanggung Village, Garut District. Observational research method and correlational descriptive design with cross-sectional approach. Purposive sampling technique for 52 respondents, mothers, and toddlers using questionnaires about factors affecting the nutritional status of toddlers. Data analysis using frequency test followed by chi-square test and odds ratio meaning α = 95%. Based on the results of univariate analysis, 57.7% did not have enough diet, 46.2% had income below minimum wage, and 36.5% had a junior high school education. Bivariate analysis showed a significant relationship between 0.000 diet and 0.001 parental income. The degree of closeness of the relationship (C) of diet with nutritional status was 0.883 of the strongest correlation categories. From the results of the study, the need for intervention from health workers to influence nutritional status, for example with educational media, pamphlets, leaflets, or brochures that are easily understood by the public about the impact of undernutrition on child development.